Optimizing allocation of catering institution establishments through the urbogeosystem GIS-analysis (case study of Kharkiv) - Безрук, Віктор; Костріков, Сергій; Чуєв, Олексій (Human Geography Journal, 2017)
The paper introduces one more example due to the urbogeosystem (UGS) function research through the GIS-tools for a megalopolis in addition to that one previously published and related to the city well-being spatial differentiation. In this case the establishment of catering institutions over the city area has been provided for consideration with GIS-tool as a urbogeosystem function. Some conceptual basics of the urbogeosystem GIS-analysis have been introduced once again too. The municipal human sphere is shortly described as a key city attribute. Visualization and analysis of the catering institution spatial distribution has been completed within an advanced GIS-interface. The urban population density, population income, and the transportation network have been defined as three key factors of the catering institution allocation. Zone burring methods have been accepted as a main tool for these key factor definition. Mentioned parameters have been processed by applying the human geography formalized methods. All key modeling buildings have been visualized in the ArcGIS user’s interface. Two scaling levels – a whole city area and its single administrative district – have been chosen for this visualization. Summarizing all introduced modeling, analysis and visualizing it is possible to conclude, that analytical abilities of the GIS together with various spatial data formats are the only tool for the variant analysis of the urban infrastructure. The two-level cartographic GIS-model of the city parcel spatial allocation with sufficient, insufficient, and desirable numbers of catering institutions must be considered as the main applied result of this research. The applied approach of the trade area definition for a catering institution has been grounded, proved, and calibrated.